Efektivitas Penegakan Hukum bagi Pelaku Pertambangan Emas tanpa Izin (Illegal Mining) - Sulaiman, Banta (PATTIMURA Legal Journal, 2023)
Introduction: Illegal Mining is Illegal Mining that is carried out without a permit so that it violates the law. Carrying out illegal mining is the same as committing a crime against State Assets, the purpose of Illegal Mining is Extraction of Natural Resources by the community or company without following operational procedures and government regulations. Purposes of the Research: The aim of the research is to examine the effectiveness of law enforcement against the crime of gold mining without a permit and to find out the obstacles in law enforcement. Methods of the Research: this research was conducted using the Juridical Empirical research method, the data used is the result of facts from the field by interviewing the Nagan Raya Police, Judges of the Suka Makmue Court and Nagan Raya Legal Academics. Results Originality of the Research: The results of the research show that law enforcement against gold miners without permits is not effective. This is evidenced by cases that always exist every year even though law enforcement has been carried out by law enforcement. The obstacle in handling this case was that when an investigation was carried out, the perpetrator had already received information.